Inclusive Growth : Measurement and Determinants - Anand, Rahul (IMF Working Papers; Working Paper, 2013)
We estimate a unified measure of inclusive growth for emerging markets by integrating their economic growth performance and income distribution outcomes, using data over three decades. Country distributions are calibrated by combining PPP GDP per capita and income distribution from survey data. We apply the microeconomic concept of a social mobility function at the macroeconomic level to measure inclusive growth that is closer to the absolute definition of pro-poor growth. This dynamic measure permits us to focus on inequality as well as distinguish between countries where per capita income growth was the same for the top and the bottom of the income pyramid, by accounting for the pace of growth. Our results indicate that macroeconomic stability, human capital, and structural changes are foundations for achieving inclusive growth. The role of globalization could also be positive with foreign direct investment and trade openess fostering greater inclusiveness, while financial deepening and technological change have no discernible effect.